Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/0300060520920417
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hidden blood loss and its influential factors in myomectomy

Abstract: Objective This study was performed to quantify hidden blood loss (HBL) and explore its influential factors in myomectomy. Methods Two hundred nine patients who underwent myomectomy by laparotomy or laparoscopy from 1 January 2017 to 31 December 2018 were analyzed. Each patient’s estimated blood volume and total blood loss (TBL) were calculated by the Nadler formula and Gross formula, respectively. The HBL was calculated by subtracting the visible blood loss (VBL) from the TBL. A multivariate linear stepwise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Moreover, when the operation time is longer, the blood may coagulate in the third space and cannot be drained out, which is usually ignored in the evaluation of VBL. 17 Therefore, we believe that reasonable control of surgery time can reduce HBL and has a positive effect on the recovery of patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, when the operation time is longer, the blood may coagulate in the third space and cannot be drained out, which is usually ignored in the evaluation of VBL. 17 Therefore, we believe that reasonable control of surgery time can reduce HBL and has a positive effect on the recovery of patients.…”
Section: Discussionmentioning
confidence: 96%
“…We hypothesized that with the extension of surgical time, the maintenance time and the dosage of muscle relaxants would be added during anesthesia, which contributes to blood infiltration into the tissue space and becoming part of HBL. Moreover, when the operation time is longer, the blood may coagulate in the third space and cannot be drained out, which is usually ignored in the evaluation of VBL 17 . Therefore, we believe that reasonable control of surgery time can reduce HBL and has a positive effect on the recovery of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative bleeding is the most common complication in a myomectomy ( 6 ). Previous research reported that the surgery duration and uterine leiomyoma number were risk factors for increased blood loss, with a longer surgery duration and removal of multiple uterine leiomyomas associated with increased blood loss ( 11 ). This research also reported that increased myomectomy-related blood loss contributed to delayed post-operative recovery by increasing the need for blood transfusions and the risk of fevers, infections and abdominal adhesions ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…HBL refers to the e ective circulation of hemoglobin and red blood cells entering the interstitial space after the operation, resulting in swelling of the a ected limb which is not directly lost to the outside world. e hazards of hidden blood loss include postoperative anemia and complications such as slow wound healing, poor functional recovery, and increased risk of infection caused by anemia [29,30]; increased risk of deep vein thrombosis in the lower extremities; increased probability of cardiovascular and cerebrovascular accidents; and subcutaneous ecchymosis [31]. Hidden blood loss falls into the category of "blood syndrome" in clinical Chinese medicine and can be traced back to " e Yellow Emperor's Classic of Internal Medicine."…”
Section: Discussionmentioning
confidence: 99%